Investigating pupillometry to detect preoperative anxiety: a pilot study - Richez, Jason; Rothschild, Pierre-Raphaël; Baillard, Christophe; Guerrier, Gilles (Frontiers in Psychology, 2024)
European Society of Anesthesia (ESA) insist on the importance of preoperative anxiety management. However its assessment relies currently on questionnaires that are long to submit and sometimes difficult to interpret. Exploring the balance between sympathetic and parasympathetic neural systems through the use of pupillometry is a promising path to identify anxiety and thus provide an objective and reproducible assessment tool. A single-center prospective observational study was conducted in a population of ambulatory ophthalmological surgery patients. Preoperative anxiety was assessed using the Surgical Fear Questionnaire (SFQ). Measurements were taken using an Algiscan® (IDMed) type pupillometer before, during and after insertion of the peripheral IV catheter. A statistical correlation test was carried out between the different evaluations of anxiety and the coefficient of variation of the pupillary diameter (VCPD). 71 patients were included in the study between July 2020 and February 2021, with a median SFQ score of 23 [IQR 11-34]. No significant statistical correlation was found between the baseline pupillary diameter or VCPD and preoperative anxiety levels. Similarly, the pupillometric variables did not differ significantly when adjusting for level of anxiety during and after painful stimulation due to canulation. More studies are necessary to explore the potential correlation between preoperative anxiety and pupillometry.